Abstract 012: First‐line Stent Retriever Versus Contact Aspiration or Combined Technique for Posterior Cerebral Artery Occlusion EVT - Piers Klein; Thanh N Nguyen; Mohamad Abdalkader; Muhammad M Qureshi; Patrik Michel; Davide Strambo; Daniel Strbian; Christian Herweh; Markus A Möhlenbruch; Silja Räty; Marta Olivé‐Gadea; Marc Ribo; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Introduction The optimal reperfusion technique in patients with isolated posterior cerebral artery (PCA) occlusion is uncertain. Previous studies in LVO and MeVO have demonstrated a correlation between good clinical outcomes and the first pass effect (FPE, eTICI 2c/3 on the first pass) but no differences in FPE rates or clinical outcomes between first‐line endovascular therapy techniques.1‐6 We compared clinical and technical outcomes with first‐line stent‐retriever (SR), contact aspiration (CA), or combined techniques in patients with isolated PCA occlusion. Methods This international cohort study was conducted at 30 sites in Europe and North America and included consecutive patients with isolated PCA occlusion and pre‐stroke modified Rankin Scale (mRS) 0‐3, presenting within 24 hours of time last seen well from January 2015 to August 2022.7 The primary outcome was the first‐pass effect (FPE), defined as eTICI 2c/3 on the first pass. Secondary outcomes included final successful reperfusion (eTICI 2b‐3), 90‐day excellent outcome (mRS 0 to 1), 90‐day functional independence (mRS 0 to 2), sICH, and 90‐day mortality. Patients treated with SR, CA, or combined technique were compared with multivariable logistic regression. This study was registered under NCT05291637. Results There were 326 patients who met inclusion criteria, consisting of 56.1% male, median age 75 (IQR 65‐82) years and median NIHSS 8 (5‐12). Occlusion segments were PCA P1 (53.1%), P2 (40.5%), and other (6.4%). Intravenous thrombolysis was administered in 39.6%. First‐line technique was SR, CA, and combined technique in 43 (13.2%), 106 (32.5%), and 177 (54.3%) patients, respectively; FPE was achieved in 62.8%, 42.5%, and 39.6%, respectively. Compared to SR, FPE was lower in patients treated with first‐line combined technique and similar in patients treated with first‐line CA (combined vs. SR: aOR 0.35 [0.016‐0.80], p=0.01; CA vs. SR: aOR 0.45 [0.19‐1.06], p=0.07). Final successful reperfusion (eTICI 2b‐3) was present in 81% of cases with no differences between treatment groups. Excellent outcome (mRS 0‐1) occurred in 30.7% of patients and functional independence (mRS 0‐2) occurred in 50.0% of patients. There were lower odds of functional independence in the first‐line CA versus SR alone group (aOR 0.52 [0.28‐0.95], p=0.04). FPE was associated with higher rates of favorable outcomes (mRS 0‐2: 58% vs. 43.4%, p=0.01; mRS 0‐1: 36.6% vs. 25.8%, p=0.05). sICH was observed in 5.6% (18/326) and mortality in 10.9% (35/326) with no differences between first‐line technique. Conclusion In patients with isolated PCA occlusion undergoing EVT, first line SR was associated with a higher rate of FPE compared to CA or combined techniques with no difference in final successful reperfusion. Functional independence at 90‐days was more likely with first‐line SR compared to CA in adjusted analyses. FPE was associated with higher rates of 90‐day excellent outcomes and functional independence. No difference in sICH or mortality was noted across the three techniques. As the endovascular field evolves to treat patients with distal vessel occlusion and milder severity of stroke, optimizing the efficacy and safety of the procedure is essential.8